Italy's banking crisis: Creditor bail-in is no panacea - Markus Demary (Institut der deutschen Wirtschaft (IW), 2016)
Italy's banks are struggling under high amounts of non-performing loans on their balance sheets and the Italian government is fighting with the European Commission over putting 50 billion Euro of problem loans into a bad bank, which needs funding of 10 billion Euro with public money. Calculations of the Cologne Institute for Economic Research reveal that banks need to be recapitalised with additional 21.7 billion Euro under this plan.
Keywords: 330